FINANCIAL STUDY OF AN INVESTMENT PROJECT IN ALGERIA: CREATION OF A COMPANY WITHIN THE FRAMEWORK OF THE NATIONAL FUNDSUPPORT FOR YOUTH EMPLOYMENT (FNSEJ) - OUABDESSELAM, Lyes (International Journal of Research -GRANTHAALAYAH, 2017)
This article proposes a financial study of a project to create a commercial enterprise through the scheme proposed by the National Agency for Youth Employment Support (ANSEJ). The company is a testing and analysis laboratory. In this study we have prepared a complete financial package and we have budgeted this project over the entire amortization period of the investment credit in accordance with the timetable set by the support system for young entrepreneurs to set up a business in Algeria. This work provides factual information to young entrepreneurs to assist them in making decisions about the implementation of similar projects.